Comparative morphology of the prostate of odontocete cetaceans: a histological, histochemical, immunohistochemical and ultraestructural study - Rivero Santana, Miguel Antonio; Suarez Santana, Cristian Manuel; Arbelo Hernández, Manuel Antonio; Sierra Pulpillo, Eva María; Espinosa de los Monteros y Zayas, Antonio; Felipe Jiménez, Idaira; Gimeno Ponce, Silvia; Consoli, Francesco; Fernández Rodríguez, Antonio Jesús (2019)
The prostate is the only male accessory gland described in cetacean. Only the anatomy and histology of the prostate of few species of these mammals has been described in the literature, and for most species this organ has not been studied. Pathologies of the cetacean’s prostate has been reported and potentially can impair the reproduction, hence the importance of investigating the normal anatomy of this organ in such species. The aim of this work was to describe the morphological characteristics of the prostate of different odontocete cetaceans by histological, histochemical, immunohistochemical and ultraestructural techniques. The prostatic gland of 47 animals of nine different species was grossly and microscopically studied. Members of the family Delphinidae, Zhiphiidae y Physeteridae were included. In general, the prostate was a musculo-glandular organ with two distinct parts: The Corpus prostatae and the Pars disseminata. In the pygmy sperm whale (Kogia reviceps) and the Cuvier’s beaked whale (Ziphius cavirostris), the prostate was a discrete gland with a small Corpus prostatae. Histologically the prostate consisted in acini and ducts, lined by a simple cuboidal epithelium, and organized in lobules. The prostates of mature and immature animals were compared. Immunohistochemical analysis was performed using low and high molecular weight cytokeratin, vimentin and prostatic specific antigen (PSA) commercial antibodies. Electron microscopy of the prostate of a bottlenose dolphin was performed and cytomorphological differences among major epithelial components of the prostatic epithelium were described. This work represents a comparative analysis of the morphology of the prostate of various cetaceans’ species.